Wina w postępowaniu w sprawach o naruszenie dyscypliny finansów publicznych a wina w postępowaniu karnym - Ogonowska, Adrianna (Wydawnictwo Naukowe UAM, 2015)
W niniejszym artykule zwrócono uwagę na obowiązujące ujęcie winy sprawcy w postępowaniu w sprawie o naruszenie dyscypliny finansów publicznych oraz w postępowaniu karnym. Jako metodę badawczą przyjęto analizę literatury przedmiotu, materiału normatywnego oraz orzecznictwa Głównej Komisji Orzekającej. Celem opracowania jest pogłębiona analiza zasady winy w kontekście wskazanych postępowań, z uwzględnieniem podobieństw i różnic między nimi.

This article presents the existing perspective of guilt in proceedings regarding the breach of public finance discipline and guilt in criminal proceedings. As the research method, the author analyzes the literature concerning the subject in question, normative material and judicature of the Main Adjudicating Committee. The article attempts to thoroughly evaluate the principle of guilt within the aspect of the aforementioned proceedings with the observance of their similarities and differences.
Guilt in proceeding in cases of violation of public finance discipline and guilt in law of criminal proceedings
Keywords: odpowiedzialność za naruszenie dyscypliny finansów publicznych; liability for the breach of public finance discipline; wina w postępowaniu karnym; guilt in criminal proceedings; okoliczności wyłączające winę; circumstances exculpating from liability